Ghrelin, not corticosterone, is associated with transitioning of phenotypic states in a migratory Galliform - Marasco, Valeria; Kaiya, Hiroyuki; Pola, Gianni; Fusani, Leonida (Frontiers in Endocrinology, 2023)
In both captive and free-living birds, the emergence of the migratory phenotype is signalled by rapid and marked increases in food intake and fuelling, as well as changes in amount of nocturnality or migratory restlessness. The metabolic hormone corticosterone and, as more recently suggested, the gut-derived hormone ghrelin have been suggested to play a role in mediating such phenomenal phenotypic flexibility given that they both regulate fuel metabolism and locomotion across vertebrate taxa. Here, using the Common quail (Coturnix coturnix) as our study species, we induced autumn migration followed by a non-migratory wintering phase through controlled changes in daylight. We thus compared plasma corticosterone and ghrelin concentrations between the two sampling phases and assessed whether these hormones might reflect the migratory state. While we found no differences in plasma corticosterone between the two sampling phases and no link of this hormone with changes in body mass, levels of food intake or migratory restlessness, the migratory birds had substantially higher levels of plasma ghrelin relative to the non-migratory birds. Furthermore, while ghrelin did not correlate with the gain in body mass over the entire pre-migratory fuelling phase (over an average of nine weeks preceding blood sampling), plasma ghrelin did positively correlate with the gain in body mass observed during the final fattening stages (over an average of three weeks preceding blood sampling). Again, variation in plasma ghrelin also reflected the amount of body mass depleted over both the long- and short-time frame as birds returned to their non-migratory baseline - lower levels of plasma ghrelin consistently correlated with larger losses in body mass. Thus, while our data do not highlight a role of the hormone corticosterone in sustaining pre-migratory fattening as shown in other bird species, they do add evidence for a potential role of ghrelin in mediating migratory behaviour and further suggest that this hormone might be important in regulating the transitioning of migratory states, possibly by promoting fuel mobilisation and usage.